2022
DOI: 10.3390/molecules27113559
|View full text |Cite
|
Sign up to set email alerts
|

Towards Bioprospection of Commercial Materials of Mentha spicata L. Using a Combined Strategy of Metabolomics and Biological Activity Analyses

Abstract: Spearmint (Mentha spicata L.) has been widely studied for its diversity of compounds for product generation. However, studies describing the chemical and biological characteristics of commercial spearmint materials from different origins are scarce. For this reason, this research aimed to bioprospecting spearmint from three origins: Colombia (Col), Mexico (Mex), and Egypt (Eg). We performed a biological activity analysis, such as FRAP, DPPH, and ABTS, inhibition potential of S. pyogenes, K. pneumoniae, E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…There have been numerous studies on the antioxidant properties of spearmint, but the results have differ significantly. While Direito et al [ 25 ] found that the antioxidant content of dried spearmint leaves was 33.96 mg AAE/g, Henao-Rojas et al [ 26 ] measured 19.63 mg AAE/g. Additionally, different values for peppermint can be found in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been numerous studies on the antioxidant properties of spearmint, but the results have differ significantly. While Direito et al [ 25 ] found that the antioxidant content of dried spearmint leaves was 33.96 mg AAE/g, Henao-Rojas et al [ 26 ] measured 19.63 mg AAE/g. Additionally, different values for peppermint can be found in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…The literature data on spearmint's polyphenol content also shown significant differences. While Kaloteraki et al [ 29 ] measured 39.61 mg GAE/g, Henao-Rojas et al [ 26 ] reported values of 11.83 and 17.81 mg GAE/g. For peppermint, Oh et al [ 27 ] reported a polyphenol content of 33.68 mg GAE/g, while Jeong et al [ 30 ] discovered polyphenol contents ranging from 55.23 to 98.27 mg GAE/g for peppermints from various countries.…”
Section: Resultsmentioning
confidence: 99%